Analyzing the Accessibility of Trolley Bus Stops in the City of Salzburg - Subedi, Sushmita; Pandit, Roman (Technical Journal, 2024)
Public transport promotes sustainable mobility by enhancing connectivity, safety, comfort and health. The location, type, condition and spacing of stops play a pivotal role in determining the accessibility to public transport. Poor accessibility to public transport can lead to increased cost and time of travel, poor mobility, traffic congestion and social exclusion. This study uses Multi Criteria Analysis to provide a holistic measure of accessibility in terms of Transit Accessibility Index (TAI) for all the trolley bus stops in the city of Salzburg. Five quantitative indicators are combined and weighted appropriately to obtain the final accessibility score. An overall accessibility assessment is performed to further classify the bus stops into five performance categories based on their final accessibility score. Ideal Point Method is employed to determine the values of indicators for the ideal bus stop and compare the values with those of the existing stops. The result from the analysis shows that the most accessible trolley bus stops are located in the core region of Salzburg city near the city center and the main train station. This kind of analysis is crucial for sustainable transport planning and thus helps to promote smart mobility and better habitability of the city.